Public Policy Failure (Case Study of Medan City Regional Regulation Number 5 of 2022 Regarding the Determination of Zoning for Street Vendor Activities in Medan City) - Batubara, Azwar Azmi; Badaruddin, Badaruddin; Irmayani, Tengku (PT FORMOSA CENDEKIA GLOBAL, 2025)
Medan as one of the largest cities in Indonesia and the center of the economy in North Sumatra is certainly not free from the problem of unemployment. Unresolved unemployment, limited new job opportunities and the pressure of economic needs to survive have caused some people to look for alternative jobs outside the formal sector. The informal sector that is widely engaged in by people in Medan City is Street Vendors (PKL). This study uses descriptive research with a qualitative approach. The results of the study indicate that the Failure of Public Policy on Determining Street Vendor Zoning in Medan City is Due to the Inability to Form a Special Task Force Approved by the BAPPEDA Service Based on the Systemic Failure Theory of Hudson, Hunter, and Peckham.